PENERAPAN MODEL PEMBELAJARAN PROBLEM BASE LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS 3 SEKOLAH DASAR PADA PELAJARAN MATEMATIKA MATERI BILANGAN CACAH 1-1000 - Nova Febriana Savitri; Dewi Tryanasari; Juli Sugianingsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT Mathematics is the science of organized structures, mathematics discusses facts and relationships, and discusses space and form. In mathematics learning, problem solving is the most important part of mathematics learning objectives. Mathematics lessons in elementary school have a purpose such as mentioning that there are 5 objectives contained in mathematics learning, one of the five purposes is so that students can solve mathematical problems including the ability to understand problems, compile mathematical models, solve models and interpret the solutions obtained. Problem Base Learning is learning where using problems in real or real events in students' lives so that students can solve a problem, think creatively and critically and students can get an essential understanding. This study aims to find out how capable students are in solving mathematical problems in the number 1 – 1000 material by using the PBL (Problem Base Learning) learning model in grade III students of SDN 02 Madiun Lor consisting of 15 students. The type of research used in this study is the Classroom Action Research (PTK) method. The use of the PTK method is because the researcher aims to overcome problems regarding students' problem-solving abilities in mathematics subjects in the number 1 – 1000 material by observing and evaluating the improvement of students' abilities in this phase to be more effective and systematic. Based on the pre-cycle percentage, data was obtained that only 3 students could achieve good scores on the criteria guidelines, while 12 students or 80% of them had not achieved the expected scores. Then in the first cycle, there has been an increase of around 8 students or 53% who have achieved grades with good predicates in the assessment guidelines, while the rest have not reached the expected target. Entering the second cycle, there was a fairly good increase, namely 12 students or 80% of them had reached the target expected in the criteria guidelines, and the remaining 3 students who had not been able to achieve it. Based on the results that have been obtained, the application of the Problem Base Learning learning model is very influential in improving problem-solving skills for grade III elementary school students.